Study on Strength Characteristics and Microstructure of Cement-modified Expansive Soil - WANG Pei; SONG Xinjiang; XU Haibo (Renmin Zhujiang)
This paper conducts the compressive strength test and scanning electron microscope oncement-modified expansive soil, establishes the three-dimensional microstructure model of expansivesoil with the help of GIS technology and calculates the three-dimensional porosity, and analyzesthe change law of micro-pores of expansive soil by adding cement. The results show that cement hasgood modification effect on expansive soil, and the compressive strength increases with theincrease of cementcontent.The GIS technology is used to realize the 3D Sence model based on theSEM image of cement-modified expansive soil, which can visually and truly show the soilparticle microstructure. Comparative results show that the method of quantitative analysis of soilmicrostructure based on GIS is feasible, with high calculation accuracy. The research resultsprovide basic parameters for cement-modified expansive soil.